Smart Government-Based Governance through Digital Transformation of Public Services: Experience of Surabaya City Government, Indonesia - Priyowidodo, Gatut; Indrayani, Inri Inggrit; Yogatama, Astri (Universitas Medan Area, 2024)
This research aims to explore Smart Governance in local government institutions. The literature review shows that some models have been developed to explain Smart Government. However, systematic research on Smart Government through the Digital Transformation of Public Services still needs to be developed. This research used a qualitative approach with a phenomenographic method. Phenomenography focuses on three things. First, it focuses on interest. Second, it is content-oriented. Third, it describes the conceptions of various aspects of their reality. Data collection through direct observation and interviews with bureaucratic officials (Head of Service), stakeholders, academics, and online service users. The stages of data analysis include three aspects, namely interpreting data (structure and meaning of data) and data categorization/coding (variations in understanding and empirical manner), as well as formulating results (identification of conception and outcome space) and making research reports. The findings of this research show that Smart or M-Government is an Essential Necessity: The evolution toward intelligent government in the digital era is no longer a choice but a historical necessity. The convergence of technological advancements in internet-based information technology and the increasing public demands for top-tier services has made competent government imperative. The city has also made strides in digital transformation, achieving digital people, platforms, processes, public services, and workspaces, accompanied by ten sub-components. This comprehensive approach to digital governance ensures that nearly all public services, including healthcare, education, and infrastructure, are accessible via digital platforms. Surabaya's commitment to diverse digital service platforms reinforces the city's dedication to staying abreast of digital technological advancements.